Assessing the potential of REDD+ in a production mangrove forest in Malaysia using stakeholder analysis and ecosystem services mapping. (December 2016) - Aziz, Ammar Abdul; Thomas, Sebastian; Dargusch, Paul; Phinn, Stuart
Abstract: Mangrove forests are ecologically important and carbon-rich coastal ecosystems that provide direct and indirect livelihood support for coastal communities. In recent years there has been increased discussion in the policy and scientific communities over how to include mangrove forests in climate change mitigation initiatives such as REDD+. There are a number of challenges to establishing a successful REDD+ project in mangrove areas, with land tenure and stakeholder entitlements arguably the most challenging. This study examines how REDD+ approaches might be applied to better balance timber production and conservation objectives in the Matang Mangrove Forest Reserve (MMFR), a 40, 466 ha mangrove forest area in Malaysia. Stakeholder profiles and needs are linked with ecosystem services to develop an integrated profile of this complex social-ecological system, which has been managed for timber production for more than 100 years, and has recently revealed evidence of declining ecosystem health. The results provide insights into how REDD+ might be operationalised in existing forest areas with traditions of multiple uses, potentially contributing to improved social-ecological outcomes for forests and their diverse stakeholders.